T Transformasi Pendidikan Islam: Studi Komparatif Sistem Pengajaran di Pesantren Tradisional dan Pesantren Modern: Transformasi Pendidikan Islam: Studi Komparatif Sistem Pengajaran di Pesantren Tradisional dan Pesantren Modern - Permadi, Muhammad Arrafi Muzhaffar; Sya'ban, Wahyudin Khairul; Hilalludin (Sekolah Tinggi Agama Islam Al-Muntahy, 2025)
Pesantren is one of the oldest Islamic educational institutions in Indonesia that has an important role in preserving Islamic values ​​and shaping the character of the nation. Along with the development of the era, globalization, and the demands of modernization of education, pesantren have transformed into two main models, namely traditional pesantren (salafiyah) and modern pesantren (khalafiyah). This study aims to compare the two models in order to identify their respective characteristics, advantages, and challenges. The study used a descriptive qualitative approach with a literature study method reinforced by interviews with pesantren caretakers in Yogyakarta and East Java. The results of the study showed that traditional pesantren emphasize the deepening of religious knowledge through classical methods such as sorogan and bandongan, and uphold the spiritual relationship between teachers and students. Meanwhile, modern pesantren integrate the national curriculum with the pesantren curriculum, apply interactive technology-based learning methods, and use a structured evaluation system. This comparison confirms that both models have complementary advantages. Therefore, an integrative approach is needed that is able to maintain the spiritual and moral values ​​of traditional pesantren while adopting modern learning innovations. Thus, Islamic boarding schools can continue to exist, be relevant, and be able to produce graduates who are religious and competent in the global era.